The The Perfect Blend: How Non-Physical Work Environment and Work Life Conflict Contribute to Employee Performance - Muthii' ahthurahmah; Agus Frianto (Universitas Negeri Surabaya, 2026)
This study aims to examine the impact of work-family conflict and non-physical work environment on fluctuations in employee performance, providing strategic insights for a public utility company in the clean water sector to optimize its human resource management. This research offers additional insights by illustrating how highly harmonious horizontal relationships may unexpectedly reduce individual independence by leading individuals to rely on peer assistance. The approach used in this study is quantitative, with saturated sampling, so the entire population of 74 people was used as respondents. Primary data were collected via structured questionnaires and analyzed using multiple linear regression analysis through SPSS version 25. The findings of this study indicate that work-family conflict has a significant negative impact on employee performance, suggesting that higher levels of role conflict are associated with a decline in professional output. In contrast, the non-physical work environment has a significant positive impact on employee performance, indicating that harmonious interpersonal relationships and effective internal communication are vital drivers of productivity. The implications of this study emphasise the importance of stress management to prevent work-family conflict, as well as improving communication and work relationships to support employee performance.